Pengembangan Desa Wisata Purbayan Kecamatan Kotagede Provinsi Daerah Istimewa Yogyakarta Melalui Peran dan Partisipasi Lembaga Desa Wisata Institute - Risqy indra Adhitya, Risqy indra Adhitya; Margaretta Andini Nugroho, Margaretta Andini Nugroho (Electronic Journal of Social and Political Sciences (E-SOSPOL), 2025)
The development of tourism villages is being encouraged by the Government. One of the institutions in Indonesia that helps develop tourism villages is Lembaga Desa Wisata Institute (LDWI). LDWI designs, develops and implements tourism development activities in a participatory manner. One of the villages fostered by LDWI is Purbayan Tourism Village which has interesting tourism potential. This study discusses the role and participation of LDWI in developing Purbayan Village as a Tourism Village. The type of data is qualitative which is the result of interviews with related institutions. Secondary data collection through the collection of documents related to the research. Determination of informants using purposive sampling techniques. The role and participation of LDWI in the stakeholder position are as Facilitators and Accelerators. Facilitators are stakeholders with the aim of providing facilities such as training activities, mentoring, and discussion forums. Accelerators are stakeholders with the aim of accelerating and implementing program design